Gestational diabetes mellitus – more than the eye can see – a warning sign for future maternal health with transgenerational impact - Massalha, Manal; Iskander, Rula; Hassan, Haya; Spiegel, Etty; Erez, Offer; Nachum, Zohar (Frontiers in Clinical Diabetes and Healthcare, 2025)
Gestational diabetes mellitus (GDM) is regarded by many as maternal maladaptation to physiological insulin resistance during the second half of pregnancy. However, recent evidence indicates that alterations in carbohydrate metabolism can already be detected in early pregnancy. This observation, the increasing prevalence of GDM, and the significant short and long-term implications for the mother and offspring call for reevaluation of the conceptual paradigm of GDM as a syndrome. This review will present evidence for the syndromic nature of GDM and the controversies regarding screening, diagnosis, management, and treatment.